Observational tests of hurricane intensity estimations using GPS radio occultations. Issue 4 (25th February 2014) - Vergados, Panagiotis; Luo, Zhengzhao Johnny; Emanuel, Kerry; Mannucci, Anthony J.
Abstract This study presents a novel approach to estimating the intensity of hurricanes using temperature profiles from Global Positioning System radio occultation (GPSRO) measurements. Previous research has shown that the temperature difference between the ocean surface and the eyewall outflow region defines hurricanes' thermodynamic efficiency, which is directly proportional to the storm's intensity. Outflow temperatures in the eyewall region of 27 hurricanes in 2004–2011 were obtained from GPSRO observations. These observations, along with ocean surface temperatures from NASA Modern Era‐Retrospective Analysis for Research and Applications, made it possible to estimate hurricane intensities using a simplified hurricane model. Our preliminary results are quantitatively consistent with best‐track values from the National Hurricane Center within 9.4%. As a by‐product of our study, we present for the first time GPSRO vertical temperature profiles in the vicinity of the eyewall region of hurricanes, which we compared with collocated temperature profiles from the European Centre for Medium‐Range Weather Forecasts Reanalysis Interim (ERA‐Interim). Some of the GPSRO data sets reveal a double tropopause in the vicinity of the eyewall—a characteristic that we do not see in ERA‐Interim. We conclude that GPSRO observations can be of supplementary assistance in augmenting existing data sets used in hurricane intensity estimation. GPSROs' cloud‐penetrating capability and high vertical resolution can be useful in providing soundings in the area close to the eyewall region of hurricanes revealing detailed information about their thermal structure, potentially advancing our current knowledge of their dynamics, evolution, and physics.